Experiências do projeto de extensão Orientação Sociojurídica Itinerante - Silva, Isabela Risso da [UNESP]; Mendonça, Maria Fernanda Aidar [UNESP]; Moreira, Pâmela Eunice [UNESP]; Lourenço, Taís Alessandra Sbrissa [UNESP]; Maniglia, Elisabete [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The article is about an itinerant Project that consists in a proposal to give guidance to the poor in Franca neighborhoods, going there and providing legal and social services to the people. The project is destined to people that don’t have money and don’t have a government assistance or even a private assistance, and live in a poor neighborhood. The project provides legal and social services in family law and social security law. The article will explain about the purpose, the methods and materials used, and the project results.

O trabalho em questão trata sobre o projeto de Orientação Sociojurídica itinerante, que consiste em uma proposta de atuação na comunidade de Franca, visando a prestação de serviços referentes a orientação e acompanhamento psicossociojuridico destinado a população hipossuficiente não assistidas por órgãos públicos ou particulares residentes nos bairros atendidos pelo projeto dentro das áreas referentes ao direito de família e previdenciário. Neste trabalho explicaremos os objetivos do projeto, os materiais e métodos utilizados e os seus resultados.
Keywords: Rights; Guidance; Formation; Direitos; Orientação; Formação